Sustancias decalcificantes para procesamiento de tejidos humanos de diferente constitución. - Carvajal Laguaquiza, Isabel Vanessa (2025)
This research focused on analyzing decalcifying substances used in human tissue processing to identify the most effective agents based on their usefulness and impact on different tissue types. Decalcification is a crucial step in sample preparation for histological analysis, as it allows for detailed visualization of cellular structures by removing calcium deposits without damaging the samples. A documentary, non-experimental design was adopted based on a bibliographic review of studies published between 2019 and 2025. The study population consisted of 43 scientific sources from reliable databases, including PubMed, Scielo, and Google Scholar. The final sample comprised 25 sources selected according to specific inclusion and exclusion criteria. Among the most commonly used decalcifying agents, EDTA stood out with 76.5%, followed by nitric acid (HNO) with 70.5%. Additionally, other substances were identified with 64.5%. HCl was the least used, at 27.5%. Although nitric acid is the fastest-acting agent, its use can compromise tissue quality, while EDTA, although slower and more expensive, offers better results in sample preservation. The results obtained led to the conclusion that, although nitric acid is the fastest-acting agent, its use can compromise tissue quality. In contrast, EDTA, although slower and more expensive, offers better results in sample preservation. To obtain a satisfactory tissue sample, the following are essential.